Contents of the socioenvironmental responsibility in electronic equipment and machinery trade - Bets, Mariana; Basiuk, Nadiia (Видавництво Львівської політехніки, 2017)
The purpose of the research is to determine the content of the socio-environmental responsibility of the retailers (distributors) in the process of selling electronic equipment and machinery (EEM) to solve the problem of handling electronic waste. Identification of physical commodity flows of electronic equipment and machinery allows distributors to become elements of the financial flow management system from the collection of electronic waste, which will improve its financial standing.
Keywords: retail network; social and environmental responsibility; electronic equipment and machinery